Analyse diachronique de l’etalement urbain dans le grand-lome au togo, une approche basee sur la teledetection multispectrale - Melone Like SORSY; Follygan HETCHELI (Revue Hybrides)
In the aftermath of independence, the countries of the African continent experienced strong population growth. Generalized population growth has led to the sprawl of built-up areas in cities to the detriment of green spaces. The Togolese capital has not remained on the sidelines of this upward trend in urban populations. Since then, the population of the Togolese capital has increased from 940,900 inhabitants in 1960 to 2,173,800 inhabitants in 2022 (INSEED, 2022), an annual growth rate of 43‰. This demographic pressure has led to a regression of vegetation in favor of built-up areas.